Chemodivergent assembly of ortho-functionalized phenols with tunable selectivity via rhodium(III)-catalyzed and solvent-controlled C-H activation - Haiman Zhang (Nature Portfolio, 2021)
Ortho functionalisation of phenols can be achieved using N-phenoxy amide directing groups. Here a method for chemodivergent C-H alkenylation, alkylation, carboetherification, or [3 + 2] annulation is presented, with product selectivity determined by the choice of solvent.